INTERDEPARTMENTAL COLLABORATION IN IMPLEMENTING THE BANA PELE PROGRAMME IN EKURHULENI - Moloi, Grace (My University, 2011)
The Bana Pele Programme was initiated by the Gauteng Provincial Government and implemented through the Department of Social Development, Department of Health and Department of Education. The aim of the integrated programme was to improve coordination between the departments and hence make it easier for orphaned and vulnerable children to access the necessary services. This study was conducted to establish if there is collaboration between the three departments, Social Development, Health and Education, in the implementation of the Bana Pele Programme. A qualitative approach was used and officials at management and field level from the three departments were interviewed. It was concluded that there is very little collaboration between the three departments resulting in the programme not achieving the intended objective of assisting orphaned and vulnerable children to easily access holistic services. Recommendations made include the need for role clarification, capacity building, more effective communication, an implementation strategy, community involvement as well as monitoring and evaluation
MM thesis - P&DM
Keywords: Interdepartmental collaboration; Children, Assistance to